Traumatic perforations of tympanic membrane: a study of sixty patients - Gupta, Anchal; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Traumatic perforation of the tympanic membrane can lead to hearing loss. This study was undertaken to study the etiology of traumatic tympanic membrane perforations. Methods: This hospital based retrospective observational study was conducted in the department of ENT, SMGS Hospital, Jammu from January 2018 to January 2019. A detailed clinical and otoscopic examination was done and symptoms noted. Tuning fork tests and pure tone audiometry was done in all the patients. Tympanic membrane perforations were visualized using otoscope or examination under microscope was done. A conservative management approach was adopted, except for those with bloody or watery discharge who received oral/systemic antibiotics to prevent infections. Results: 60 patients were included in the study. Maximum patients were in the age group of 21-40 years accounting for 56.7% patients. The male to female ratio was 1.4:1. The most common complaint was tinnitus (90%), followed by pain in ear (81.6%), hearing loss (56.7%), aural fullness (45%), ear bleed (16.7%) and vertigo (5%). The most common etiology was physical assault by slaps and blows to ear (40%), followed by instrumentation (syringing and foreign body removal). In 40 (66.67%), left ear was involved whereas in 20 (33.33%) right ear was involved. 51 (85%) patients showed spontaneous healing within 3 months whereas 9 (15%) showed no healing and these 15% patients underwent tympanoplasty at the end of 3 months. Conclusions: Traumatic tympanic membrane perforations have a very good prognosis if they are treated at a right time.